BMI, diet and female reproductive factors as risks for thyroid cancer: a systematic review. - Emily Peterson; Prithwish De; Robert Nuttall (PLoS ONE)
Background Thyroid cancer incidence rates have been increasing worldwide but the reason behind this is unclear. Both the increasing use of diagnostic technologies allowing the detection of thyroid cancer and a true increase in thyroid cancer incidence have been proposed. This review assesses the role of body mass index (BMI), diet, and reproductive factors on the thyroid cancer trend. Methods Epidemiologic studies of the selected risk factors up to June 2010 were reviewed and critically assessed. Results Among the thirty-seven studies reviewed and despite variation in the risk estimates, most papers supported a small but positive association for BMI (risk estimate range: 1.1-2.3 in males and 1.0-7.4 in females.). Among specific dietary components, there was no consistent association of thyroid cancer risk with iodine intake through fortification (risk estimate range: 0.49-1.6) or fish consumption (risk estimate range 0.6-2.2), nor with diets high in cruciferous vegetables (risk estimate range 0.6-1.9). A small number of studies showed a consistent protective effect of diets high in non-cruciferous vegetable (risk estimate range: 0.71-0.92). Among reproductive factors (pregnancy, parity, number of live births, use of prescription hormones, menstrual cycle regularity, and menopausal status), none were consistently associated with higher thyroid cancer risk. Conclusions BMI had the strongest link to thyroid cancer risk among those examined. Detailed examinations of population-level risk factors can help identify and support prevention efforts to reduce the burden of thyroid cancer.